“Mil siglos durará nuestra memoria”. El sustrato historiográfico de La Numancia de Miguel de Cervantes - de la Fuente de Pablo, Pablo (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The core of this work is the study of the sources used by Miguel de Cervantes while writing his tragedy entitled La Numancia, which relates events from the final stages of the Third Celtiberian War (133 BC). Did the author use primary sources or only secondary ones? Another objective of the paper is to explain that although, for the most part, the plot follows historical events, there are some points in which it departs from both geographical and historical truth. The question tackled in the paper is: what are the reasons behind breaking the process of the recreation of the historical events?